Effect of slope angle on energy performance of ground-integrated buildings on slope terrain - De Castro, M.; Gadi, Mohamed (WIT Press, 2017)
The noticeable rise in urban development and topography factors across Europe has resulted in a visible increase in the number of residential buildings being constructed in hillside areas. Several studies about ground-integrated architecture have proved that buildings can benefit from ground thermal potential, in order to reduce or eliminate the heating and cooling needs. However, only a small number of published articles tackle the potential of ground-integrated buildings on sloped terrains. The purpose of this paper is to explore the ground thermal potential of sloped terrains in temperate climates, through parametric studies using EnergyPlus as the energy modelling software. This paper looks at two main questions: firstly, how buildings are affected by terrain inclination and, secondly, which types of slope building designs are more thermally efficient, particularly the case of spilt level, amended section and cascade or step-hill designs.